The Effect of Social Interaction Learning Model, Learning Motivation, Social Attitude on The Student Learning Result - Sahudra, Tengku Muhammad; Murniati; Setiawan, Deny; Taher, Alamsyah (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to test the difference of sudents learning outcome of Geographic subject taught with social inquiry learning model, social simulation and students’ social investigation, social behavior, learning motivation of SMA in Aceh Province. The research methodology employed in his research was quasi- experimental with the design using a Non-equivalent Control Group Design method. The experimental class and the control of this research are selected randomly. The findings that there are no differences in student learning outcomes of Geography subject taught with social inquiry learning models, social simulation learning models and group investigative learning models. There are differences in the learning outcome of geography subject and different social attitude, which is a high social attitude and social attitude. There is an interaction between the learning model, social attitudes and learning motivation. There is an interaction between learning models and social attitudes. There is an interaction between learning model and learning motivation. There is an interaction between learning model and learning motivation. The research on the application of social interaction learning model to improve learning motivation, social attitude, and students learning outcome at the geographic subject of SMA in Aceh Province, Indonesia.